An overview of bio-adhesives for engineered wood products. (October 2022) - Kumar, Chandan; Leggate, William
Abstract: The use of engineered wood products (EWPs) is rapidly increasing in the building industry worldwide due to their reliable structural performance, lower weight, renewability, carbon storage, quick on-site installation, and lower levels of construction waste. The adhesives used for manufacturing the EWPs are mainly synthesised from petroleum and natural gas derived chemicals. However, increasing concerns regarding formaldehyde emissions, environmental sustainability and long term security of supply of petrochemicals are the biggest motivation for researchers to develop bio-based adhesives. The main objective of this article is to review recent advances in bio-based adhesives and their application in wood based composite products. Bio-adhesives derived from lignin, protein, tannin and starch and their reported performance are discussed. Bio-based adhesives at various stages of commercial development as reported by the industry and/or in patents are also discussed. Although bio-based adhesives provide a sustainable solution and significantly reduce formaldehyde and volatile emissions, they still pose several different limitations that hinder their industrial and commercial use. The major limitations include: 1) the availability of tannins 2) lack of adhesion for starches 3) poor water resistance for lignin and protein and 4) low strength properties mainly limiting their use to non-structural applications. However, the literature review demonstrates that various modifications, additives and cross-linkers can significantly improve various properties of bio adhesives. The paper also presents a brief summary of the advantages and disadvantages of synthetic adhesives.